2011
DOI: 10.1111/j.1751-908x.2011.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of PIXE and ICP‐AES Analyses of Aeolian Dust from Owens (Dry) Lake, California

Abstract: Particle-induced X-ray emission (PIXE) and ICP-AES can be combined to obtain a wider range of detected elements, augment previous data and ⁄ or to verify measured concentrations of heavy and trace metals in geological samples. Intercomparison of data sets generated by multiple techniques is challenging due to the differing processes and methods of each technique. Here, we compare elemental data obtained by both techniques for aeolian dust from Owens (Dry) Lake, California. Nineteen elements were detected by PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 72 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…In contrast to the "low hygroscopicity" samples, aerosols generated from the Owens Lake Crust sample produced several ion peaks consistent with soluble sodium carbonates, sodium chloride (halite), and sodium sulfates. These ion peaks include 62 Na 2 O + , which is likely due to the fragmentation of Na 2 CO 3 forming 62 Na 2 O + and CO 2 (g), similar to the ions observed for calcite, and further supported by the observation of 129 Na 3 CO 3 + in this sample. The saline-rich, erodible soil from Owens (dry) Lake, especially when collected from the surface containing efflorescent salts, has been found to contain several minerals rich in sodium carbonates, including natron (Na 2 CO 3 •10H 2 O), thermonatrite (Na 2 CO 3 •H 2 O), and trona (Na 3 HCO 3 CO 3 • 2H 2 O).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast to the "low hygroscopicity" samples, aerosols generated from the Owens Lake Crust sample produced several ion peaks consistent with soluble sodium carbonates, sodium chloride (halite), and sodium sulfates. These ion peaks include 62 Na 2 O + , which is likely due to the fragmentation of Na 2 CO 3 forming 62 Na 2 O + and CO 2 (g), similar to the ions observed for calcite, and further supported by the observation of 129 Na 3 CO 3 + in this sample. The saline-rich, erodible soil from Owens (dry) Lake, especially when collected from the surface containing efflorescent salts, has been found to contain several minerals rich in sodium carbonates, including natron (Na 2 CO 3 •10H 2 O), thermonatrite (Na 2 CO 3 •H 2 O), and trona (Na 3 HCO 3 CO 3 • 2H 2 O).…”
Section: Resultssupporting
confidence: 81%
“…consistent with previous results that indicated that this sample contained a mixture of surface salts and the underlying aluminosilicate material. 62,63 Further, this sample lacked ion peaks indicative of sodium sulfates and halite, and had low intensity peaks associated with sodium carbonates consistent with this sample representing a cement-like crust rather than an erodible, saline-rich crust. Overall, the Owens Lake Crust sample generated several ion peaks indicative of highly hygroscopic material (e.g., Na 2 SO 4 , κ ∼ 1.04; NaCl, κ ∼ 1.4; Na 2 CO 3 , κ ∼ 1.29 31,47 ), which explains the order of magnitude difference in κ between the two different samples from Owens (dry) Lake, as well as the high hygroscopicity of the Owens Lake Crust sample in comparison to the other playa samples.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The “sediment” sample represents a mixture of materials derived from both the evaporite surface and the salt-silt-clay crust directly underneath, including highly hygroscopic sodium carbonates and sodium sulfates that best explain our high values of γ N2O5 and φ ClNO2 . In contrast, the “crust” sample was a hard, white material composed of pure salts that do not fully deliquesce at the humidities used in this work. ,,, These results underscore the heterogeneity of mineral content not only across playas but also within the same playa …”
Section: Resultsmentioning
confidence: 66%
“…In contrast, the "crust" sample was a hard, white material composed of pure salts that do not fully deliquesce at the humidities used in this work. [50][51][52]74,104,105 These results underscore the heterogeneity of mineral content not only across playas but also within the same playa. 106 In contrast to the Salton Sea and the Owens Lake "crust" samples that show increasing values of both γ N2O5 and φ ClNO2 with RH, dust generated from the Black Rock Desert showed increasing yields of ClNO 2 (0.3−0.6) but a decrease in N 2 O 5 reactivity (0.07−0.02) with increasing RH.…”
Section: Environmental Science and Technologymentioning
confidence: 82%